(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Micro Small and Medium Enterprises are recognized as the engine of growth all over the world. The present paper deals with the marketing problems faced by micro small and medium enterprises in Thoothukudi District. The study has the following objectives 1. To study the socio-economic outline of the micro, small and medium entrepreneurs. 2. To find out the professional background of micro, small and medium entrepreneurs. 3. To understand the satisfaction of micro, small and medium industries among the sample respondents based on sex. 4. To analyse the marketing problems faced by the sample respondents. The study is confined to Thoothukudi district of Tamil Nadu. Both primary and secondary data have used for the present study. Secondary data were collected from the journals, publications, reports, books, unpublished Ph.D thesis, research papers and websites. The data to be analysed with the help of statistical tools like average, percentages, standard deviation, chi-square test, t test etc. It is revealed that the intended value is higher than the table value at 5 percent level, there is a relationship between the sources of finance of the micro, small and medium entrepreneurs and their marketing problems. The micro, small and medium enterprises come across many problems, chiefly insufficient finance, absence of infrastructure, absence of managerial capability, insufficient market connection and outdated equipment, though running their business. To overawed these problems Government has to take distinctive inventiveness to implement group schemes through which could be educated to have more consciousness to grow Micro, Small and Medium Industries in Thoothukudi District